Rivaroxaban Versus Enoxaparin for Thromboprophylaxis After major Gynecological Cancer Surgery: The VALERIA Trial: Venous thromboembolism prophylAxis after gynecoLogical pElvic cancer surgery with RIvaroxaban versus enoxAparin (VALERIA trial). (December 2022) - Longo de Oliveira, André Luiz Malavasi; de Oliveira Pereira, Renata Fernanda; Agati, Leandro Barile; Ribeiro, Camilla Moreira; Kawamura Suguiura, Gabrielly Yukimi; Cioni, Claudia Helena; Bermudez, Marilsa; Pirani, Márcia Bermudez; Caffaro, Roberto Augusto; Castelli, Valter; Resende Aguiar, Valéria Cristina; Volpiani, Giuliano Giova; et al.
Direct oral anticoagulants (DOACs) for venous thromboembolism (VTE) prevention after major gynecological cancer surgery might be an alternative to parenteral low-molecular-weight heparin (LMWH). Patients undergoing major gynecological cancer surgery were randomized at hospital discharge to receive rivaroxaban 10 mg once daily or enoxaparin 40 mg once daily for 30 days. The primary efficacy outcome was a combination of symptomatic VTE and VTE-related death or asymptomatic VTE at day 30. The primary safety outcome was the incidence of major or clinically relevant nonmajor bleeding. Two hundred and twenty-eight patients were enrolled and randomly assigned to receive rivaroxaban (n = 114)or enoxaparin (n = 114). The trial was stopped due to a lower-than-expected event rate. The primary efficacy outcome occurred in 3.51% of patients assigned to rivaroxaban and in 4.39% of patients assigned to enoxaparin (relative risk 0.80, 95% CI 0.22 to 2.90; p = 0.7344). Patients assigned to rivaroxaban had no primary bleeding event, and 3 patients (2.63%) in the enoxaparin group had a major or CRNM bleeding event (hazard ratio, 0.14; 95% CI, 0.007 to 2.73; P = 0.1963). In patients undergoing major gynecological cancer surgery, thromboprophylaxis with rivaroxaban 10 mg daily for 30 days had similar rates of thrombotic and bleeding events compared to parenteral enoxaparin 40 mg daily. While the power is limited due to not reaching the intended sample size, our results support the hypothesis that DOACs might be an attractive alternative strategy to LMWH to prevent VTE in this high-risk population.